An endosiRNA-Based Repression Mechanism Counteracts Transposon Activation during Global DNA Demethylation in Embryonic Stem Cells - Berrens, Rebecca V; Andrews, Simon; Spensberger, Dominik; Santos, Fátima; Dean, Wendy; Gould, Poppy; Sharif, Jafar; Olova, Nelly; Chandra, Tamir; Koseki, Haruhiko; von Meyenn, Ferdinand; Reik, Wolf (Cell stem cell, 2017)
Erasure of DNA methylation and repressive chromatin marks in the mammalian germline leads to risk of transcriptional activation of transposable elements (TEs). Here, we used mouse embryonic stem cells (ESCs) to identify an endosiRNA-based mechanism involved in suppression of TE transcription. In ESCs with DNA demethylation induced by acute deletion of Dnmt1, we saw an increase in sense transcription at TEs, resulting in an abundance of sense/antisense transcripts leading to high levels of ARGONAUTE2 (AGO2)-bound small RNAs. Inhibition of Dicer or Ago2 expression revealed that small RNAs are involved in an immediate response to demethylation-induced transposon activation, while the deposition of repressive histone marks follows as a chronic response. In vivo, we also found TE-specific endosiRNAs present during primordial germ cell development. Our results suggest that antisense TE transcription is a "trap" that elicits an endosiRNA response to restrain acute transposon activity during epigenetic reprogramming in the mammalian germline.